Towards a Better Understanding of Lawyers’ Judgmental Biases in Client Representation: The Role of Need for Cognitive Closure - James H. Stark; Maxim Milyavsky (Washington University Journal of Law & Policy, 2019)
Previous research demonstrates that lawyers and law students are, on average, prone to overconfidence bias and self-serving judgments of fairness when they take on a representative lawyering role. This is the first study to investigate individual differences in susceptibility to these biases. Expanding on two previous experiments, and utilizing as our sample 468 law students from twelve geographically diverse U.S. law schools, we examined whether differences in students’ Need for Cognitive Closure (NFC) — a motivational desire for clear answers over ambiguity — would affect both their judicial outcome predictions and their assessments of the “fair settlement value” of a simulated personal injury case when assigned randomly to the role of plaintiff’s or defendant’s counsel. We also investigated whether high- or low-NFC scores would have any effect on the efficacy of a “consider-the-opposite” (“list the weaknesses of your case”) prompt given to half of our subjects in an effort to de-bias these assessments. We found that a high need for closure intensifies self-serving bias in both students’ judicial predictions and fair value assessments, and that bias in students’ judicial predictions could be mitigated through debiasing interventions, even with students high in need for closure. Bias in fairness assessments persisted, despite de-biasing prompts.
Keywords: bias; judgment; client representation; Need for Cognitive Closure; NFC